A study on the translation of culture-specific items in character depiction in the English version of Pu Songling‟s Liaozhai Zhiyi - Yi, Shuihan; Ng, Chwee Fang; Abdul Halim, Hazlina (Sciedu Press, 2024)
The characterization through literary translation is crucial to the international dissemination and reception of literary works. Nevertheless, the research on the translation of character depiction in Liaozhai Zhiyi greatly falls behind other translation themes of Liaozhai Zhiyi. This study is intended to explore the translation of culture-specific items (CSIs) in character depiction in Liaozhai Zhiyi from Chinese to English, within the framework of character‟s three dimensions: physiological, sociological and psychological. This study reveals the shifts in the characterization by investigating translator‟s strategies, and the significant integration of CSIs and character depiction. The findings demonstrates that the translator‟s choice of strategies influences the rendering of character depiction. It is found that the character depiction in the original text of Liaozhai Zhiyi is more mysterious, whereas in the translated text, it seems to possess a stronger sense of intimacy. This study suggests that translators thoroughly consider the culture-specific elements in character depiction, and take into account the combination of multi-strategies. It is hoped that this study contributes to the research field of character depiction translation in Liaozhai Zhiyi, and sheds light on the translation of ancient Chinese classics.